Features and Partial Derivatives of Bertalanffy-Richards Growth Model in Forestry - Lei, Y. C.; Zhang, S. Y. (Nonlinear Analysis: Modelling and Control, 2004)
The Bertalanffy-Richards growth model is employed more than any other models for forest growth and yield modelling. However, its features have not completely been recognised. As a result, misunderstanding of the model still appears in some papers published in forest journals. A study by [1] is cited here as an evidence of the misunderstanding. This paper tries to explain different features of the Bertalanffy-Richards growth model based on the different conditions of the allometric parameter and introduces an assessment software to easily get the partial derivatives with respect to each parameter when more complex techniques (e.g., the Marquardt method) are employed to estimate parameters of any nonlinear models. This paper indicates that [1] study appears some unreasonable evidences of nonlinear growth models from a forestry perspective.